W poszukiwaniu eklektycznego paradygmatu edukacji głuchych - Tomaszewski, Piotr; Moroń, Ewelina (Studia Edukacyjne, 2018)
In recent years, changes in the approach to deafness and, hence, in the education of the deaf and hard of hearing have been occurring around the world, including Poland. Deafness is increasingly perceived as a sociocultural phenomenon and not merely as a medical one, while sign language is seen as a natural language that can be used in deaf schools and by large numbers of d/Deaf people. Nevertheless, it seems at present that both deafness models are incompatible with each other for ideological reasons although they are concurrent, the medical model being dominant and the sociocultural one being alternative. For that reason, both the d/Deaf community and the deaf education still contend with significan problems related to the language policy, discrimination based on deafness (audism), sign language (linguicism), disability (ableism) or the specificityof conflictsamong the d/Deaf themselves (deafism).All this will be illustrated in this paper, along with suggested possible solutions.